Model Probabilistik Fuzzy Goal Programming Berdistribusi Pareto dengan Urutan Prioritas pada Permasalahan Produksi Kue - Eka Susanti; Oki Dwipurwani; Robinson Sitepu; . Wulandari; Liani Natasia (Jurnal Matematika, 2018)
Yulis’s home industry is one of the Small and Medium Bussiness (UKM) on Palembang city. Yulis’s home industry produces bolu kukus, kue lapis, kue pare, kumbu kacang, srikaya, and wajik. Most of cakes that will be produced by Yuli is still based on the cake sale on the last day, so that the profit is still not optimal condition. This research aims to create preemptive priority additive approach to Fuzzy Goal Programming Probabilistic (PFGP) model with Pareto distribution for maximize profits, minimize the production of perishable cake, and maximize best sellers cake. The results are obtained maximum profit is Rp. 8.488.569 on a week , the amount of perishable cake is 1,295 pieces on a week, and optimal production for best seller cake as much as 8,489 pieces on a week.